A Note on Physical and Mechanical Properties of Cinnamomum camphora (Cinnamon) from New Forest, Dehra Dun (U.P.) - Gupta, V. K.; Negi, Y. S. (Indian Forester, 1982)
Physical and mechanical tests were done in green and kiln dry conditions on small clear specimens obtained from 9 logs of cinnamomum camphora received from New forest, Dehra Dun. The relults obtained have been compared with Teak. It is found that valuel are lower than standard teak in general. Estimated values based on strength specific gravity formulae hive also been compared with observed values in green condition. The observed values are higher than estimated. Safe working stresses and suitability indices based on specific gravity have also been reported and compared with the corresponding values of Teak.